Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Di Hotel BW Luxury Jambi - Nindi Sri Hasanah; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted based on the results of the author's observations when carrying out industrial field practice at the BW Luxury Jambi hotel and the background because there is still substandard employee performance which is thought to be due to organizational culture. This study aims to determine the effect of organizational culture (X) on employee performance (Y) at BW Luxury Jambi hotel. This type of research is descriptive quantitative classified as causal associative research with a survey method that shows cause and effect. The number of samples in this study were 80 respondents. Data collection techniques by distributing questionnaires using a Likert scale that has been compiled. Analysis techniques in this study use simple linear regression and also the coefficient of determination. The results concluded that organizational culture (X) is in the good category (53.75%), employee performance (Y) is in the good category (52.5%). Based on the simple linear regression test results obtained that organizational culture has a significant effect on employee performance with a regression coefficient of 1.514 sig value. 0.000 <0.05, it means that every increase of 1 unit of organizational culture, the participation value increases by 1.514. The regression coefficient is positive, which can be stated that the direction of the influence of variable (X) on variable (Y) is positive. Based on the results of the R square test, the R Square value is 0.206, which can be interpreted that the effect of variable X on variable Y is 20.6%. While 79.4% is influenced by other factors not discussed in this study.